Utilization of coal bottom ash to improve thermal insulation of construction material - Torkittikul P. (2017)
© 2015, Springer Japan. Concerns with sustainable solid waste management and recycling have become increasingly prominent in all sectors of the economy. In light of this, this research investigates the possibility of utilizing coal bottom ash (waste from thermal power plants) as a substitute for fine aggregate in mortar and concrete. The chemical composition, microstructure and mechanical properties, including workability, density, water absorption, compressive strength and thermal conductivity, of mortar and concrete incorporating coal bottom ash in partial and full replacement of sand were investigated, and the results were compared to the data for conventional mortar and concrete. The results show that the density of mortar and concrete was noticeably decreased with increasing coal bottom ash content. In addition, despite the permeable pore space of mortars and concretes increasing with increasing levels of coal bottom ash, the use of coal bottom ash does not significantly affect the compressive strength of concrete. Furthermore, the mortars and concretes containing coal bottom ash exhibited good thermal insulation properties; thermal conductivity values decreased significantly with increasing coal bottom ash content, and the thermal conductivity of mortar and concrete with 100 % coal bottom ash showed a decrease of 68.61 and 46.91 %, respectively, as compared to that of the control.